Optimalisasi Peran Guru dalam Meningkatkan SDM Masyarakat Desa Geger Melalui Bimbingan Belajar - Khoirul Faizin; Abd. Hafid; Lukman Khoirin; Sugito (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2025)
This study examines the implementation of the Asset-Based Community Development (ABCD) approach as a model for sustainable community empowerment in Geger Village, Kedungadem District, Bojonegoro Regency. The ABCD approach emphasizes identifying and mobilizing local strengths, including social networks, human resources, and natural assets, as the foundation for development rather than relying on external assistance. The purpose of this research is to analyze how the ABCD stages—inculturation, discovery, dream, design, define, and destiny—were applied in establishing a community-based tutoring program (BIMBEL) aimed at improving children’s academic performance and strengthening social participation in education. Using a participatory method involving mothers, youth, community groups, and local leaders, the program provided structured learning activities, subject-based lessons, study guidance, and collaborative learning practices. The findings reveal significant positive changes, including increased student motivation, improved confidence in learning, higher attendance, and the emergence of stronger community engagement. The study also identifies several challenges such as the limited availability of qualified tutors, diverse cognitive abilities among students, and inconsistent study habits. However, strong parental support, adequate learning facilities, and active social structures contributed greatly to the program’s success and continuity. Overall, the research concludes that the ABCD approach effectively promotes community-driven educational initiatives and fosters the creation of a new social institution that enhances local human resources. The community-based tutoring program represents a long-term social investment that is expected to shape a knowledgeable, disciplined, and competitive young generation in Geger Village.